Groups in action evolution and challenges - Corey, Gerald; Corey, Marianne Schneider; Haynes, Robert (Australia: Thomson/Brooks/Cole, 2005)
Consists of two different interactive program. The first program entitle'evolution of a group' and the second program is'challenges facing group leaders'
Keywords: Group counseling; Psychotheraphy; Group counseling; Group psychotherapy